2x+3 is the answer.................................................................
Im not sure i understand the question, but i think 25/7
3∅ can be rewritten as (2∅+∅)
sin(3∅) = sin(2∅ + ∅<span>)
Opening brackets on the right hand side;
= sin2</span>∅ cos ∅ + cos2∅sin<span>∅
</span><span>This simplifies to;
= 2sin</span>∅cos^2∅ + sin∅ (1- 2sin^2∅<span>)
= sin</span>∅ (2cos^2∅ + 1 - 2sin^2∅<span>)
= sin</span>∅ (2(1 - sin^2∅) +1-2sin^2∅<span>)
= 3sin</span>∅ - 4sin^3<span>∅</span>
The sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
<h3>Sum of expressions</h3>
Expressions are equations separated by mathematical signs. This expressions are known to contains certain unknowns
Given the following expression
10x^2 +7x+6 and 6x + 5
We are to take the sum of both expression to have:
f(x) = 10x^2 +7x+6 + 6x + 5
Collect the like terms
f(x) = 10x^2 + 7x + 6x + 6 + 5
f(x) = 10x^2 + 13x + 11
Hence the sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
Learn more on sum of functions here: brainly.com/question/11602229
#SPJ1